Phytoremediation: Treating Euthrophic Lake at KotaSAS Lakeside, Kuantan by Aquatic Macrophytes - Muhammad Haziq, Jamil; Farah Amalina, Ishak; Abdul Syukor, Abd Razak; Sulaiman, S.; Siddique, Md. Nurul Islam; Woon, S. X. R. (2019)
This investigation was embraced ex-situ to investigate the capability of the submerged plants' water hyacinth (Eichornia crassipes) and water lettuce (Pistia stratiotes L.) as phytoremediation aquatic macrophytes for nutrients removal from a eutrophic lake situated at KotaSAS Lakeside surrounded by residential area as the risk of algae bloom can be avoided. The present of mankind activities such as sewage runoff and agricultural towards water bodies, the eutrophication process being speed up. The capability of these plants to evacuate certain parameters not just supplements while additionally including BOD5, COD, TSS, Turbidity, and heavy metals. The technique for investigation of lake water was alluded by Standard Method for Examination of Water and Wastewater. Water lettuce displayed extraordinary nitrate removal effectiveness up to 94% however this plant species shrivelled from week 2 of the examination because of an absence of nitrate supply and caused an expansion in phosphorus concentration. Then, water hyacinth indicates relentless evacuation productivity with a normal of 82% for nitrate and phosphorus. Other than that, water hyacinth indicates 88% and 72% of TSS and turbidity expulsion effectiveness which can improve the clarity of lake water. With this accomplishment gained in phytoremediation innovation utilizing water hyacinth, it is of most significance for this innovation to be executed in bigger scales in the future.